Pentingnya Pendidikan Karakter Kewarganegaraan Remaja dalam Memelihara Karakteristik Remaja dan Citra Bangsa Indonesia - Mutia Kamila, Aisya; Dhiya Ulhaq, Khairunnisa; Rasendriya Putri, Nathaya; Kembara, Maulia Depriya (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2024)
This research was conducted with the aim of knowing how important civic education is to maintain the image of the Indonesian nation. This research was conducted, because along with the development of the digital age, in the process of teenage self-discovery, there is often a fading of civic character education contained in adolescents which sucks the degradation of moral quality and character possessed by adolescents due to various existing factors.  This will be a problem in maintaining the image of the nation and the civic character of adolescents in Indonesia. The research was conducted using mixed methods, namely qualitative and quantitative. The research was conducted by distributing questionnaires and survey activities to teenagers as the research target. Then, data analysis was carried out to obtain research results. After conducting the research, the results obtained are that the character of Civic Education is considered very important and influential for the image of the Indonesian nation. With this character education, teenagers can have a good mindset, attitude and behavior in accordance with civic values and various aspects. With this, public high school students in Bandung must implement attitudes and actions that are in accordance with the character of citizenship. With the support of the family, community and school environment. As well as the government as a provider of solutions and strategies for these problems. Such as conducting socialization by providing good knowledge to adolescents about the values of Pancasila and citizenship that must be instilled early.